"Gay Equals White"? Racial, Ethnic, and Sexual Identities and Attitudes Toward LGBT Individuals Among College Students at a Bible Belt University. Issue 8 (13th October 2018) - Worthen, Meredith G. F.
Abstract : While past research has certainly explored a variety of correlates of attitudes toward lesbian, gay, bisexual, and transgender (LGBT) individuals, the current study is among the first in an emerging line of inquiry that examines attitudes toward each of these groups separately utilizing an intersectional framework with special attention to racial, ethnic, and sexual identities. Using a college sample of students from the Bible Belt of the United States (N = 1, 940), I investigated the roles of racial and ethnic identities (Caucasian/White, African American/Black, Asian/Pacific Islander, Native American/Alaskan Native, other race, and Hispanic/Latinx), religiosity, patriarchal gender norms, parental perspectives, and the intersections among these identities and experiences as they relate to attitudes toward LGBT individuals among heterosexual (n = 1, 551) and LGB respondents (n = 389). This moves beyond explorations of White heterosexual people's attitudes about "homosexuals" (i.e., away from a focus only on gayness and Whiteness) and expands to include non-White LGB people's LGBT attitudes. Overall, results indicate that racial, ethnic, and sexual identities play a significant role in southern college students' LGBT attitudes, and these patterns are further complicated by interacting cultural experiences with religiosity, patriarchy, and family dynamics. Campus policy and program implications are provided.